TINDAK ILOKUSI DALAM WAWANACARA BILL GATES DAN STEVE JOBS - Ngala, Dorna Volin; Rattu, Jultje A.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dorna Volin Ngala1Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dr. Jultje Aneke J. Rattu, SS, M,Mktg2Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dr. Garryn Ch. Ranuntu, S.PM.Hum3Â Â Â This research entitled â€œIllocutionary Act on the Interview of Bill Gates and Steve Jobsâ€ is a pragmatic analysis focusing on speech act, especially, illocutionary act. This research is an attempt to indentify and classify types and analyze and describe functions of illocutionary act used in the Interview of Bill Gates and Steve Jobs. This research is conducted by using descriptive method where the focus on this research is identifying illocutionary acts on the Interview. Furthermore, this research is done by using theory from Austin (1962) to analyze and classify those illocutionary acts according its function. The result of this research shows that there are 34 illocutionary acts found on the press conference and all the data are divided into five types of illocutionary acts and its function, such as: verdictives (declare, date, calculate, hold as metter as fact, estimate, and value), excersitives (ordering, appointing, directing, advising), commissives (declare an intention, promising, espouse, and oppose), behabitives (compliment and thank), expositives (giving a statement and giving a view).______________________________________Keywords: Pragmatic, Illocutionary Act, Bill Gates, Steve Jobs, Interview